Factors related to job satisfaction among South Korean dentists - Lai CS, Shieh TY, Yang YHC, Chong MY, Hung HC, Tsai CC (Blackwell Synergy, 2006)
The purpose of this study was to provide useful data for a future abstinence project by identifying the factors related to quitting areca (betel) quid chewing.